BISNIS SEBAGAI GERAKAN DAKWAH DAN DAMPAKNYA BAGI KESEJAHTERAAN SOSIAL MENURUT TAFSIR AL-MISBAH - Kris Nandang; Suciyadi Ramdhani (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
This paper aims to describe business in the view of Islam according to Ibn Ubaid in Al-Amwal. The focus studied is business as a da'wah movement that has an impact on the social welfare of the people as exemplified by the role model of Muslims, Prophet Muhammad SAW. Through literature review, data collection comes from books and articles and analyzed and triangulation of data. Through this method, it can be explained that Islam accommodates every human effort in managing his life through business. It is based on teachings that are attentive to social life so that an Islamic business culture is formed which leads to social welfare through three main assets as a guide, namely, profit (material) and benefit (non-material), growth and blessings. Quraish Shihab shows that Islam's attention to every business that contains benefits for others deserves appreciation in one's spiritual quality. In addition, economic stability and good governance of state administration are factors for creating prosperity by adhering to the principles of monotheism, the benefit of mankind, the unity of humanity, the belief in the unity of the world and the hereafter.